Pengembangan Buku Cerita Digital “Cinta Tanah Air” Untuk Anak Usai Dini - Benny Hendriana; Amelia Vinayastri; Reny Harpiyani (Universitas Negeri Padang, 2022)
The rapid development of the flow of globalization makes it easier for cultures from abroad to enter Indonesia and makes it possible for future generations to forget their own culture, including early childhood, which is the nation's next generation. Therefore, it is necessary to have a learning media for early childhood instilling the character of love for the homeland, namely through the medium of digital love story books for the homeland. The purpose of this development is to introduce ways to love the homeland and also to instill the character of love for the homeland in children from an early age. This research uses the R&D (Research and Development) method with the ADDIE development model. This digital storybook media was tested by material experts, media experts, teachers, and guardians of PAUD Nusa Indah students. The results of the assessment of media experts were: 90% (very valid), material experts 95% (very valid), teachers and parents 98% (very valid). Based on the results of the assessment, it shows that digital story books are very good as a medium for early childhood learning in instilling the character of love for the homeland.